Cell–fibronectin interactions and actomyosin contractility regulate the segmentation clock and spatio-temporal somite cleft formation during chick embryo somitogenesis - Gomes De Almeida, Patrícia (2022)
Fibronectin is essential for somite formation in the vertebrate embryo. Fibronectin matrix assembly starts as cells emerge from the primitive streak and ingress in the unsegmented presomitic mesoderm (PSM). PSM cells undergo cyclic waves of segmentation clock gene expression, followed by Notch-dependent upregulation of meso1 in the rostral PSM which induces somite cleft formation. However, the relevance of the fibronectin matrix for these molecular processes remains unknown. Here, we assessed the role of the PSM fibronectin matrix in the spatio-temporal regulation of chick embryo somitogenesis by perturbing (1) extracellular fibronectin matrix assembly, (2) integrin–fibronectin binding, (3) Rho-associated protein kinase (ROCK) activity and (4) non-muscle myosin II (NM II) function. We found that integrin–fibronectin engagement and NM II activity are required for cell polarization in the nascent somite. All treatments resulted in defective somitic clefts and significantly perturbed meso1 and segmentation clock gene expression in the PSM. Importantly, inhibition of actomyosin-mediated contractility increased the period of hairy1/hes4 oscillations from 90 to 120 min. Together, our work strongly suggests that the fibronectin–integrin–ROCK–NM II axis regulates segmentation clock dynamics and dictates the spatio-temporal localization of somitic clefts.